Penerapan Prinsip-Prinsip Syariah Pada Fintech: Studi Kasus PT Dana Syariah Indonesia - Dontes Putra; Rozalinda Rozalinda; Ahmad Wira (Pusat Riset dan Inovasi Nasional, 2024)
As ia icountry iwith ithe ilargest iMuslim ipopulation iin ithe iworld, ioverall isharia ifintech iin iIndonesia ihas igreat ipower ibecause iit ican iprovide isolutions ifor ithe iMuslim icommunity ithat icannot ibe iprovided iby iconventional ifinancial iinstitutions. iThis iresearch idiscusses iwhether isharia ifintech iis iin iaccordance iwith iSharia iprinciples. iThe iaim iof ithis iresearch iis ito ifind iout iwhether isharia ifintech iis iin iaccordance iwith iIslamic iprinciples. iThis iresearch iis ibased ion iqualitative iresearch iwith ia iliterature istudy imethod i(library iresearch). iThe iresearch iresults ishow ithat ithe isuitability iof ithe isharia ifintech iagreement, iDana iSyariah iin ithe iadministrative iaspect iis iin iaccordance iwith ithe iprovisions iin iforce iin iIndonesia. iDana iSyariah's isharia ifintech iagreement iwith ipeer ito ipeer ilending iis iin iaccordance iwith isharia iprinciples iand iin iaccordance iwith ithe iFatwa iof ithe iNational iSharia iCouncil iof ithe iIndonesian iUlema iCouncil i(DSN iMUI)